The Impact of Social Skills Training for Novice Teachers on the Academic Motivation of Their Students - Farhadian , Ali; Saif, Ali Akbar; Asadzadeh, Hassan (KMAN Counseling & Psychology Nexus, 2023)
Objective: This study aimed to examine the effectiveness of social skills training for novice teachers on the academic motivation of their students. Methodology: The research utilized a quasi-experimental design with random assignment, involving 32 student-teachers from basic science disciplines at the Farhangian University, divided into experimental and control groups. The student-teachers were selected based on having lower social skills compared to their classmates. The statistical population included both the student-teachers and their students, with 628 students from 32 classes taught by these novice teachers forming the sample. Measurement tools consisted of two standardized tests: the Riggio and Canary Social Skills Test and the Hermans Academic Motivation Questionnaire. Findings: The researchers’ hypothesis regarding the effectiveness of social skills training for student-teachers on the academic motivation of their students was confirmed, with a mean difference of 7.04 in favor of the experimental group and a confidence level of 99%. Conclusion: The findings demonstrated that social skills training for student-teachers positively impacts their students’ academic motivation.